Coping Strategies of Pregnant Women with Detected Fetal Anomalies in Iran: A Qualitative Study - Morvarid Irani; Talat Khadivzadeh; Seyyed-Mohsen A; Hosein Ebrahimipour (Wolters Kluwer Medknow Publications, 2019)
Background: Progressing technology has increased the detection of fetal abnormalities in the pregnancy. Detection of fetal abnormalities during pregnancy can cause significant social, physical, psychological, and emotional stress. The aim of this study was to explore the coping strategies of Iranian pregnant women with detected fetal anomalies. Materials and Methods: This qualitative content analysis study was conducted on two referral centers for fetal anomaly. The data were collected from April 2017 to January 2018 in Mashhad (Iran) through individual, semistructured, in-depth interviews with 25 pregnant women with a prenatal diagnosis of fetal anomalies. Data were analyzed using conventional content analysis based on Graneheim and Lundman's approach. Results: As a result of data analysis, the four categories of seeking information, religiousness and spirituality, cognitive avoidance, and seeking social support, and 12 subcategories emerged. Seeking information consisted of the four subcategories of personal search, visiting different doctors, performing various diagnostic tests and sonography, and seeking peers' experiences. Religiousness and spirituality contained the three subcategories of praying, acceptance of destiny, and reliance on faith. Cognitive avoidance consisted of the two subcategories of avoiding negative information and avoiding situations that remind them of their problem. Seeking social support contained the three subcategories of getting support from family, getting support from friends, and getting support from others. Conclusions: The findings showed that pregnant women with detected fetal anomalies reported a variety of coping strategies. Therefore, it is important that healthcare providers encourage mothers to use strategies that are likely to be more effective.